On inequalities of Hermite-Hadamard-Mercer type involving Riemann-Liouville fractional integrals - Abdeljawad, Thabet; Ali, Muhammad Aamir; Mohammed, Pshtiwan Othman; Kashuri, Artion (AIMS mathematics, 2021)
The goal of this article is to establish many inequalities of Hermite-Hadamard-Mercer type involving Riemann-Liouville fractional operators. We also establish some related fractional integral inequalities connected to the left side of Hermite-Hadamard-Mercer type inequality for differentiable convex functions. Further remarks and observations for these results are given. Finally, we see the efficiency of our inequalities via some applications on special means.